Comparison study of facilities maintenance between government and private highrise residential building / Nor Fadilah Abd Halim - Abd Halim, Nor Fadilah (2009)
Facilities Management defines facilities management as 'the practice of coordinating the physical workplace with the people and work of an organizations', For the purpose, the facilities management is 'an integrated approach to operating, maintaining, improving and adapting the buildings and infrastructure of an organization in order to create an environment that strongly supports the primary objectives of that organization'. Maintenance management is very important part in building to ensure that the building can extent their life period. Maintenance is a continuous protective care of the fabric, contents and setting of a place and must be distinguished from repair. Maintenance may be taken either preventive maintenance or corrective maintenance. Preventive maintenance is in anticipation of failure and corrective maintenance is carried out to restore the building to an acceptable standard after failure, For that reason, facilities maintenance for high-rise building is one of the most important things to consider in order to managing a building.